Electrical characterisation of epitaxial AlN/Nb2N heterostructures grown by molecular beam epitaxy. Issue 14 (1st July 2016) - Downey, B.P.; Katzer, D.S.; Nepal, N.; Meyer, D.J.; Storm, D.F.; Wheeler, V.D.; Hardy, M.T.
Abstract : Initial electrical characterisation of epitaxial AlN/Nb2 N heterostructures grown by molecular beam epitaxy on 6H‐SiC substrates is presented. Metal–insulator–metal (MIM) devices of varying diameter were used for current–voltage and capacitance–voltage ( C – V ) measurements at various temperatures. From C – V measurements, a dielectric constant of 10.1 was extracted along with a linear dependence of capacitance on temperature of 0.02 nF/cm 2 /°C. Leakage current was determined to be consistent with a Poole–Frenkel conduction mechanism at electric fields >1.25 MV/cm with an extracted trap ionisation energy of 0.82 eV. Electric field breakdown ranged between 3.4 and 5.6 MV/cm with some dependence on the diameter of the MIM device. These initial findings demonstrate the potential for high‐power devices based on AlN.